A classification prognostic score to predict OS in stage IV well-differentiated neuroendocrine tumors. Issue 6 (June 2018) - Pusceddu, Sara; Barretta, Francesco; Trama, Annalisa; Botta, Laura; Milione, Massimo; Buzzoni, Roberto; De Braud, Filippo; Mazzaferro, Vincenzo; Pastorino, Ugo; Seregni, Ettore; Mariani, Luigi; Gatta, Gemma; et al.
Abstract : No validated prognostic tool is available for predicting overall survival (OS) of patients with well-differentiated neuroendocrine tumors (WDNETs). This study, conducted in three independent cohorts of patients from five different European countries, aimed to develop and validate a classification prognostic score for OS in patients with stage IV WDNETs. We retrospectively collected data on 1387 patients: (i) patients treated at the Istituto Nazionale Tumori (Milan, Italy; n = 515); (ii) European cohort of rare NET patients included in the European RARECAREnet database ( n = 457); (iii) Italian multicentric cohort of pancreatic NET (pNETs) patients treated at 24 Italian institutions ( n = 415). The score was developed using data from patients included in cohort (i) (training set); external validation was performed by applying the score to the data of the two independent cohorts (ii) and (iii) evaluating both calibration and discriminative ability (Harrell C statistic). We used data on age, primary tumor site, metastasis (synchronous vs metachronous), Ki-67, functional status and primary surgery to build the score, which was developed for classifying patients into three groups with differential 10-year OS: (I) favorable risk group: 10-year OS ≥70%; (II) intermediate risk group: 30% ≤ 10-year OS < 70%; (III) poor risk group: 10-year OS <30%. The Harrell C statistic was 0.661 in the training set, and 0.626 and 0.601 in the RARECAREnet and Italian multicentric validation sets, respectively. In conclusion, based on the analysis of three 'field-practice' cohorts collected in different settings, we defined and validated a prognostic score to classify patients into three groups with different long-term prognoses.